PENGARUH KEBERTERIMAAN LAYANAN PEER TO PEER LENDING KEPADA UMKM SEBAGAI PENGGUNA DENGAN MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Kurniawan, Taufan Adi; Wardani, Dewi Kusuma; Widhayati, Lucianna (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2019)
This study conducted to determine the effect of Perceived Ease of Use, Perceived Usefulness,Trust and user’s attitude towards the acceptability of peer to peer lending system. The method used in this study was the technology acceptance model (TAM). This study used quantitative data using a questionnaires, while the population in this study were UMKMs in Daerah Istimewa Yogyakarta. The result of this study showed that Perceived Ease of Use, Perceived Usefulness, Trust and user’s attitude were significantly related for the acceptance of peer to peer lending system in UMKM users..